Analisis pendapatan usaha kecil dan menengah di Kabupaten Tanjung Jabung Barat (studi kasus usaha keripik tempe di Desa Serdang Jaya Kecamatan Betara) - Nur Abni Yusmah; Yulmardi Yulmardi; Adi Bhakti (Konsentrasi Ekonomi Sumberdaya Alam dan Manusia, Prodi Ekonomi Pembangunan, Fakultas Ekonomi dan Bisnis, Universitas Jambi, 2020)
The purpose of this study is to determine and analyze the socio-economic characteristics of tempe chip business in Serdang Jaya Village, Betara District and the effect of production, production costs and labor use on the income of tempe chip business in Serdang Jaya Village, Betara District. The data used in this study are secondary data. The analytical method used is quantitative descriptive analysis. The analytical tool used is multiple linear regression. The results showed the effect of production (PRO), production costs (BP) and the use of labor (PTK) together or partially had an influence on the income of tempe chip entrepreneurs in Serdang Jaya Village (Y) at a significance level of 5%.